A inserção da mulher jovem no mundo do trabalho e suas conexões com o processo de formação profissional - Silva, Josiane Emilia da (2009)
This work is the result of an investigation about the entrance of the young woman in the world of work and its connections with the professional education process. In order to see the contradictories mediations of the difficulties of entrance of the young woman in the world of work, some studies, field researches were done with teenagers and youngsters from the computer and citizenship and also the preparatory to enter in the university and citizenship courses, from Casa da Juventude Pe. Burnier (youth‟s house Priest Burnier), It‟s an institute of education, support and research in issues about youth, it offers professional education process to teenagers and youngsters from 14 to 29 years old from Goiania, preparing them to enter in the world of work. The people held by the institute are teenagers and youngsters from the border of Goiania. They come from the public schools and belong to low financing conditions‟ family. In this research, I focused on the female people from 15 to 24 years old, analyzing 35 questionnaires with students from computer and preparatory for college courses and interviewing with 25 students. After careful analysis of the data collected from the enrollment questioner to apply the courses, I identified and organized the information about the social-cultural and economic reality of the students. According to the information, it‟s possible to realize that there is a similar difficult to enter the labor space for the female students from both projects above mentioned. The consequence of this research from the analysis of the enrollment questionare, made me work with a focal group, to realize from the topics elaborated the percurse of the difficulties and the experiences of the girls to enter and face this world of work. This work, tries to in a critical e ethical way have an overview of the entrance of young women in the world of work and also tries to visualize the real conditions of the young people‟s work in the labor space.